Performativity and gameplay: gender, race, and desire amongst a team of League of Legends players - Whitfield, Kirsten/Waker (Linguistics, 2021)
Computer gaming is an important and growing form of popular media that has many cognitive and social benefits for players. It has also developed a reputation for being a white-male pastime and barring access for people who fall outside of that social grouping. While statistics show that this is increasingly not the case, certain games, particularly those that fall under the category of eSports, do attract largely male player bases. League of Legends is one such game. With Butler's Performativity Theory as a theoretical starting point, a qualitative sociolinguistic study was undertaken into the gendered dynamics of a male-dominated clan of League of Legends players. The data, collected primarily via audio-recordings of player interactions between games, is used as the basis for a sociolinguistic case study that looks at how performativity plays itself out in an environment that is characterised by a strong gender bias. With a focus on a Coloured female gamer in a League of Legends team, this paper explores the ways in which she and her teammates construct their own genders within this particular sociolinguistic context. The relationship between identity and desire, which has been a point of debate in sociolinguistics, is discussed in the context of the clan's interactions. Here I focus on the debate between Cameron and Kulick on the one hand and Bucholtz and Hall on the other. The paper looks into ways in which desire and identity interact with each other during sociolinguistic interaction. Moreover, issues around the construction of gender, race and sexuality are central to the study. The paper uses the data collected to look into the ways that social identities are collaboratively constructed, and contested. The discussion shows that while the team members replicate the gender binary, they do so by simultaneously reifying and challenging gendered norms. The study provides a compelling look into the ways in which gender identities are played with in interaction, and sheds some light on the fluidity of performative identity while simultaneously sketching out the ways that such performance is limited by its environment.